Exhaust Emission Assessment with Energy Structural Evolution in Transportation Network - Hongzhi Lin (Discrete Dynamics in Nature and Society)
Electric vehicles have become a ubiquitous form of transportation in the transition period from the petroleum era to the electricity era. The development of electric vehicles is of great interest to researchers, policy-makers, consumers, and industries. However, the dynamic environmental impact assessment along with energy structural evolution in transportation network is still wondering as the vehicular exhaust emissions are highly dependent on their market shares and working conditions. In this paper, a Markov chain model is formulated to represent the transition process between traditional internal combustion engine vehicles (ICEVs), plug-in electric vehicles (PEVs), and hybrid electric vehicles (HEVs), with which the dynamic market penetration level of three vehicle types can be predicted. Therefore, the amount of pollutants can be figured out based on their market penetration level and network traffic conditions. For a given transportation network, system equilibrium is proposed to calculate network traffic conditions. It is a four-step sequential model with feedback which can be solved by method of successive averages (MSA) with decreasing weights effectively. A simulation experiment using Nguyen–Dupuis network demonstrates the effect of the proposed method. It is found that the proposed method is effective to assess the dynamics of environmental impacts as the penetration of electric vehicles into transportation system. The method is particularly operable for policy designs stimulating the development of electric vehicles.